GR_GERICHTE SK1 2022 37 vom 14. Februar 2024 , 1C_170/2024 vom 05.03.2025 - GR Gerichte (2024)
grobe Verletzung von Verkehrsregeln gem. Art. 34 Abs. 4 SVG und Art. 35 Abs. 2 SVG i.V. mit Art. 90 Abs. 2 SVG | Strassenverkehrsgesetz SVG